Selective targeting of CREB‐binding protein/β‐catenin inhibits growth of and extracellular matrix remodelling by airway smooth muscle. (25th October 2016) - Koopmans, Tim; Crutzen, Stijn; Menzen, Mark H; Halayko, Andrew J; Hackett, Tillie‐Louise; Knight, Darryl A; Gosens, Reinoud
Abstract : Background and Purpose: Asthma is a heterogeneous chronic inflammatory disease, characterized by the development of structural changes (airway remodelling). β‐catenin, a transcriptional co‐activator, is fundamentally involved in airway smooth muscle growth and may be a potential target in the treatment of airway smooth muscle remodelling. Experimental Approach: We assessed the ability of small‐molecule compounds that selectively target β‐catenin breakdown or its interactions with transcriptional co‐activators to inhibit airway smooth muscle remodelling in vitro and in vivo . Key Results: ICG‐001, a small‐molecule compound that inhibits the β‐catenin/CREB‐binding protein (CBP) interaction, strongly and dose‐dependently inhibited serum‐induced smooth muscle growth and TGFβ1‐induced production of extracellular matrix components in vitro . Inhibition of β‐catenin/p300 interactions using IQ‐1 or inhibition of tankyrase 1/2 using XAV‐939 had considerably less effect. In a mouse model of allergic asthma, β‐catenin expression in the smooth muscle layer was found to be unaltered in control versus ovalbumin‐treated animals, a pattern that was found to be similar in smooth muscle within biopsies taken from asthmatic and non‐asthmatic donors. However, β‐catenin target gene expression was highly increased in response to ovalbumin; this effect was prevented by topical treatment with ICG‐001. Interestingly, ICG‐001 dose‐dependently reduced airway smooth thickness after repeated ovalbumin challenge, but had no effect on the deposition of collagen around the airways, mucus secretion or eosinophil infiltration. Conclusions and Implications: Together, our findings highlight the importance of β‐catenin/CBP signalling in the airways and suggest ICG‐001 may be a new therapeutic approach to treat airway smooth muscle remodelling in asthma.